German Multicenter Real-World Registry of Stenting for Superficial Femoral Artery Disease: Clinical Results and Predictive Factors for Revascularization. (August 2014) - Krankenberg, Hans; TÜbler, Thilo; Sixt, Sebastian; Fischer, Matthias; Schmiedel, Rainer; Schulte, Karl-Ludwig; Balzer, Jörn O.; Kieback, Arne; Fiehn, Eduard; Wittenberg, GÜnther; Ali, Tammam; Tiefenbacher, Christiane; et al.
Purpose: To investigate nitinol stent treatment of superficial femoral artery (SFA) lesions and the impact of different risk factors on the need for clinically driven target lesion revascularization (TLR) in a large, real-world population of claudicants. Methods: Patients presenting with symptomatic SFA stenosis >70% were consecutively enrolled in the 13-center MARIS prospective registry ( ClinicalTrials.gov identifier NCT01067885). There was no restriction on lesion length, thus leading to the inclusion of a real-world as well as high-risk patient cohort. The 998 participating patients (657 men; mean age 67.4±9.2 years) had 1050 lesions treated with the same nitinol stent type. The mean lesion length was 9.5±9.6 cm (range 0.5–44; median 8.0); more than a third of the lesions (450, 42.9%) were total occlusions. The primary endpoint was the need for clinically driven target lesion revascularization (TLR) at 12 months. Results: Acute technical success was achieved in 1042 (99.2%) lesions. Restenosis occurred in 187 (23.7%) and reocclusion in 79 (10.0%) lesions at 12 months. The primary endpoint of TLR at 12 months was reached by 136 (17.2%) patients. The periprocedural complication rate was 5.4%. Independent predictors of TLR were female gender [odds ratio (OR) 0.5, 95% confidence interval (CI) 0.3 to 0.7, p<0.001] and lesion length >20 cm vs. 10 cm (OR 2.7, 95% CI 1.1 to 6.6, p=0.029) and 10–20 cm vs. 10 cm (OR 1.9, 95% CI 1.0 to 4.1, p=0.047). Conclusion: Stent implantation in the SFA is safe and associated with favorable acute and midterm results in a real-world setting. Lesion length and female gender were identified as independent risk factors for TLR.